Ablation of Carotenoid Cleavage Enzymes BCO1 & BCO2 Alters Gut Microbial and Plasma Metabolomic Profiles in High Refined Carbohydrate Diet-Fed Mice. (14th June 2022) - Daniels, Michael; Huang, Neil; Dolnikowski, Gregory; Matuszek, Gregory; Lim, Ji Ye; Matthan, Nirupa; Wang, Xiang-Dong
Abstract: Objectives: β-Carotene-15, 15′-oxygenase (BCO1) and β-carotene-9′, 10′-oxygenase (BCO2) cleave carotenoids to form vitamin A or apo-carotenoid species. Beyond these roles, BCO1 and BCO2 have been implicated in modulating lipid, cholesterol, and oxidative stress-related processes, yet less is known about their combined influence on shaping gut microbial and plasma metabolic profiles. Current intake of refined carbohydrates and added sugars exceeds the recommendations within the Dietary Guidelines for Americans, which may contribute to the development of nonalcoholic fatty liver disease (NAFLD). In the present study, we aimed to uncover whether mice with systemic ablation of BCO1-/-/BCO2-/- (DKO) display distinctive phenotypes in response to a high refined carbohydrate diet (HRCD) model of NAFLD. Methods: Male, six-week-old C57BL/6J wild type mice (WT) and DKO mice were fed a chow diet or a HRCD (66.5% carbs including sucrose) for 24 weeks. We used fecal and plasma samples to respectively perform 16S rDNA sequencing, and both targeted and untargeted metabolomics using our UHPLC-QTOF-MS platform, a targeted Biocrates MxP Quant 500 kit, and a complimentary untargeted analysis of phospholipids from the METLIN database. Data were analyzed using QIIME2-DEseq2, MetaboAnalyst 5.0, MassHunter Qualitative Analysis, and MicrobiomeAnalyst. Results: HRCD-fed WT and DKO mice developed similar levels of hepatic steatosis although DKO mice had significantly higher hepatic levels of malondialdehyde (MDA). Interestingly, in both chow-fed and HRCD-fed DKO mice, plasma adiponectin and hepatic bile acids were significantly lower compared to respective WT groups. Our metabolomics data revealed that DKO mice displayed significant alterations in ceramide, cholesterol ester, triglyceride, and phospholipid classes under both chow and HRCD conditions. Additionally, when compared to HRCD-fed WT mice, HRCD-fed DKO mice displayed significantly reduced alpha diversity and possessed significant compositional differences based on Bray Curtis dissimilarity measures. Conclusions: BCO1/BCO2 DKO mice display altered metabolomic and gut microbial profiles. Carotenoid cleavage enzymes affect diverse physiological processes, which involve lipid metabolism and the gut microbiome. Funding Sources: USDA/ARS and NIFA/AFRI.